A apropriação do global para fins locais: as representações da identidade gaúcha em comunidades virtuais do Orkut - Pieniz, Monica (2009)
This study focuses on the social representations of gaucho s identity in virtual communities on Orkut. Definitions of virtual community, local culture, social representations, identity and cyberculture are part of this study. The objectives are to measure the occurrence of Orkut communities involving gaucho s culture; to examine the main representations for gaucho s identity in descriptive, verbal and iconic texts from the corpus selected for qualitative analysis; to analyze the peripheral representations of gaucho s identity recurrent in the corpus; to investigate the profile of the owners based on age, city, gender and their virtual communities. In the methodology, firstly we used qualitative research methods, analyzing aspects of virtual communities focusing on the gaucho s culture. This qualitative research was carried out in the light of the discourse analysis, and the categories of time, space and person. The corpus was selected considering verbal and iconic texts of the communities and the profile of the owners, based on a quantitative parameter. The data show that the main representations for gauchos in the corpus are originated from the culture conveyed by Movimento Tradicionalista Gaúcho (MTG) and Centros de Tradições Gaúchas (CTG). The peripheral representations found are those considered innovative if compared to the traditionalism. They are the minority in the corpus and contain the largest number of members. In the system of the main representations and the peripheral representations, it was found the reference to territory, institutions, rural sociability, and the occurrence of meaning production defined by the cavalry spirit. In the verbal and iconic texts as well as in the profiles of the communities owners, characteristics related to the topic of the community are predominant. It gives support to the hypotheses that the appropriation of global with local aims reinforces social representations of ordinary people s identities influenced by the cyberculture, and that these identities can be affected by elements from peripheral representations.